Jamming Attacks in Wireless Sensor Networks: A State of the Art Approach. - Fernandez-Beltran, M; Adasme-Soto, P; Valencia-Cordero, C (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper is a review of the state of the art, in which aspects related to security in the physical layer of wireless sensor networks are considered. For such purposes, the main characteristics of this type of networks are reviewed, as well as the main interference attacks that they may suffer, in addition to anti-interference strategies focused mainly on those based on optimization algorithms and game theory. From the literature review, it is concluded that the aspects related to effectiveness, efficiency and practical issues are key, highlighting that the techniques presented have been developed and implemented in simulation environments, which pose a challenge in the design of security strategies in this type of networks from a practical point of view. © 2024 IEEE.